Bayesian methods for evidence synthesis and decision making in Health Technology Assessments - Schmitz, Susanne (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
In this thesis statistical methodologies to improve reimbursement decisions in healthcare are developed. The allocation of healthcare resources is a very topical issue in the current economic climate. Given a limited healthcare budget it is important to distribute scarce resources fairly and efficiently. To aid decision making, new technologies are formally evaluated regarding their costs and benefits prior to reimbursement in so-called Health Technology Assessments. The work conducted in this thesis feeds into the evidence synthesis as well as the decision theoretic aspect of this process.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.